2013
DOI: 10.1371/journal.pone.0076359
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Clostridium perfringens Type B in an Individual at First Clinical Presentation of Multiple Sclerosis Provides Clues for Environmental Triggers of the Disease

Abstract: We have isolated Clostridium perfringens type B, an epsilon toxin-secreting bacillus, from a young woman at clinical presentation of Multiple Sclerosis (MS) with actively enhancing lesions on brain MRI. This finding represents the first time that C. perfringens type B has been detected in a human. Epsilon toxin’s tropism for the blood-brain barrier (BBB) and binding to oligodendrocytes/myelin makes it a provocative candidate for nascent lesion formation in MS. We examined a well-characterized population of MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
150
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(155 citation statements)
references
References 71 publications
1
150
0
4
Order By: Relevance
“…Third, it is possible that C. perfringens might participate in more than one CNS autoimmune disease. In this regard, one year after we identified the potential link between C. perfringens and NMO,3 C. perfringens was implicated in MS pathogenesis 19. Another study found that Clostridium species within clusters XIVa and IV, which do not contain C. perfringens (a member of cluster I), are reduced in relapsing–remitting MS patients 20.…”
Section: Discussionmentioning
confidence: 97%
“…Third, it is possible that C. perfringens might participate in more than one CNS autoimmune disease. In this regard, one year after we identified the potential link between C. perfringens and NMO,3 C. perfringens was implicated in MS pathogenesis 19. Another study found that Clostridium species within clusters XIVa and IV, which do not contain C. perfringens (a member of cluster I), are reduced in relapsing–remitting MS patients 20.…”
Section: Discussionmentioning
confidence: 97%
“…Environmental exposures such as stress, season, sunlight, vitamin D and recent viral infections have been linked to risk of relapse, with the presumed pathway(s) being through immune system modulation. Interestingly, these environmental factors also influence the gut microbiota which likewise modulates the immune system which is known to be affected in MS. 1,2,3 Further, differences have been observed in the gut microbiota of individuals with and without MS, 3,5-8 including pediatric MS. 5 Pediatric MS offers opportunity to study disease processes in the very early stages of MS, relatively close to the actual biological onset of disease, potentially limiting confounders. We explored the association between gut microbiota profiles in early pediatric MS and subsequent relapse risk.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, toxinotype B has been detected in a human with a clinical presentation of multiple sclerosis, providing clues for environment triggers of the disease [4]. C. perfringens toxinotype D affects mainly sheep and lambs but also causes infections in goats and calves [2,3].…”
Section: Introductionmentioning
confidence: 99%